Combination of Thyroxine with Vitamin B12 on Motor Nerve Conduction Study of Ulanr Nerve in Newly Diagnosed Hypothyroid Female - Ahmed, Farjana; Sultana, Nayma; Chowdhury, Md Arifuzzaman; Banik, Shyamal Chandra; Saha, Kartik Chandra; Rahman, Mahaboba (Medicine Today, 2022)
Introduction: Combination of thyroxine with vitamin B12 can improve the motor nerve conduction study of ulnar nerve in newly diagnosed hypothyroid female. Objectives: To observe the combined effects of thyroxine with vitamin B12 on motor nerve conduction study of ulnar nerve of newly diagnosed hypothyroid female Materials and Methods: This prospective interventional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC) between July’ 2015 to June’ 2016 on 40 newly diagnosed hypothyroid female. Among them, 20 hypothyroid patients received only thyroxine (HT-T4 ) and another 20 hypothyroid patients received combined therapy of thyroxine with vitamin B12 (HT-C) for 90 consecutive days. Motor 2 nerve conduction study of ulnar nerve was studied to observe the electrophysiological status and vitamin B12 level was also estimated to observe its level by using standard method. The statistical analysis was done by ANOVA test, paired, independent sample ‘t’ test and Chi-square (χ 2 ) test as applicable. Results: In this study, latency was significantly decreased, amplitude and NCV were significantly increased in motor functions of ulnar nerve of hypothyroid patients after 90 days supplementation of combined therapy of thyroxine with vitamin B12 in comparison to those of their pre-supplemented state and also to those of patients with only thyroxine treatment. Conclusion: The combination of thyroxine with vitamin B12 can reduce the symptoms of hypothyroid neuropathy and accelerate the nerve conduction velocity of motor functions of ulnar nerve more efficiently than the treatment with thyroxine alone. Medicine Today 2022 Vol.34(2): 117-120